Correlation analysis of serum LAP, GDGF, and Ferritin in the prognosis of acute myeloid leukemia: Serum LAP, GDGF, and Ferritin in the prognosis of AML - Ma, Naixia; Zhou, Rui; Ge, Yaqi; Huan, Yahong (Journal of Medical Biochemistry, 2026)
Objective To look into the correlation analysis between blood levels of Latency associated peptide (LAP), Glioma-derived growth factor (GDGF), Ferritin, Neutrophil/Lymphocyte ratio, and Albumin/Fibrinogen ratio and the prognosis of patients with acute myeloid leukemia (AML). Methods The study group consisted of 384 AML patients who were hospitalized to the hospital between May 2022 and October 2024, whereas the control group was made up of 192 healthy people who were examined physically while they were there. The levels of serum LAP, GDGF, and Ferritin and the Neutrophil/Lymphocyte ratio and Albumin/Fibrinogen ratio were compared. Following their discharge, the study group’s participants were monitored for a total of 12 months. Patients having a favorable prognosis and those with a bad prognosis were divided into two groups. The factors predicting a poor prognosis in AML patients were examined using multivariate logistic regression and a comparison of the clinical data from the two groups. Receiver operating characteristic (ROC) curves were developed to evaluate the predictive significance of LAP, GDGF, Neutrophil/Lymphocyte ratio, Albumin/Fibrinogen ratio, and Ferritin for a poor prognosis in AML patients. Results The GDGF level, Ferritin, Neutrophil/Lymphocyte ratio, and Albumin/ Fibrinogen ratio were all higher than those in the control group (P<0.05), although the study group’s serum LAP level was lower (P<0.05). Among the AML patients, 116 had a poor prognosis (poor prognosis group), and 268 had a good prognosis (good prognosis group). The group with a bad prognosis had lower levels of GDGF, Ferritin, Neutrophil/Lymphocyte ratio, and Albumin/Fibrinogen ratio (P<0.05), although the group with a good prognosis had greater levels of serum LAP (P<0.05). Multivariate logistic regression analysis showed that elevated serum LAP levels were independent protective factors for poor prognosis in AML patients (P<0.05), while elevated serum GDGF and Ferritin levels, along with elevated Neutrophil/Lymphocyte ratios and Albumin/Fibrinogen ratios, were independent risk factors for poor prognosis in AML patients (P<0.05). According to the ROC curve study, the areas under the curve (AUCs) of LAP, GDGF, Ferritin, the Neutrophil/Lymphocyte ratio, and the Albumin/Fibrinogen ratio for forecasting a poor prognosis in AML patients were 0.747, 0.811, 0.804, 0.783, and 0.845, respectively. Conclusion Serum LAP levels are decreased in AML patients, whereas GDGF, Ferritin, Neutrophil/Lymphocyte ratio and Albumin/Fibrinogen ratio levels are increased. Additionally, each of the aforementioned signs has some prediction value for the poor prognosis of individuals with AML and is an independent influencing factor.